2012
DOI: 10.1248/yakushi.132.933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flavin Adenine Dinucleotide on Ultraviolet B Induced Damage in Cultured Human Corneal Epithelial Cells

Abstract: This study evaluated the eŠects of ‰avin adenine dinucleotide (FAD) on ultraviolet B (UV-B)-induced damage in cultured human corneal epithelial (HCE-T) cells. The cultured HCE-T cells were treated with 0.003125 0.05% FAD before exposure to 80 mJ/cm 2 UV-B. Cell viability was measured 24 h after UV-B irradiation using the MTS assay. Reactive oxygen species (ROS) were detected 30 min after UV-B irradiation using 5-(and-6)-chloromethyl-2',7'-dichlorodihydro‰uorescein diacetate acetyl ester. Apoptosis was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The high level of intracellular ROS, which is the product of oxidative stress in the cornea induced by UV-B, resulted in ER dysfunction and cell apoptosis. 30,31 BiP/glucose-regulated protein 78 (Grp78) was confirmed as an ER stress-related marker. The current study showed an opposite trend between the expression of Prdx6 and Grp78, which indicated that downregulated expression of Prdx6 resulted in high ER stress.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The high level of intracellular ROS, which is the product of oxidative stress in the cornea induced by UV-B, resulted in ER dysfunction and cell apoptosis. 30,31 BiP/glucose-regulated protein 78 (Grp78) was confirmed as an ER stress-related marker. The current study showed an opposite trend between the expression of Prdx6 and Grp78, which indicated that downregulated expression of Prdx6 resulted in high ER stress.…”
Section: Discussionmentioning
confidence: 96%
“…The current study showed an opposite trend between the expression of Prdx6 and Grp78, which indicated that downregulated expression of Prdx6 resulted in high ER stress. Scoltock et al 30 and Sakamoto et al 31 reported that high ER stress could cause apoptosis. Our results of increased expression of Grp78 in HCECs with decreased Prdx6 expression are consistent in demonstrating increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%